KARAKTER MORFOLOGI DAN FISIOLOGI TAPAK DARA (Vinca rosea L.) PADA BEBERAPA CEKAMAN AIR - SUKARMAN, SUKARMAN; DARWATI, I.; RUSMiN, D. (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
Morphological and physiological characteristics of Vinca at di fferent water stress levelsVinca (Vinca rosea L.) is one of the important medicinal crops as the sources of raw materials for traditional medicines. Its alkaloid is believed can reduce the risk of cancer, blood tension and diabetes diseases. Recently, vinca is only grown as ornamental plant in the garden, therefore, its cultivation methods is limited, especially its water stress tolerance, lite purpose of this experiment was to study the effect of water stess on the morphological and physiological characteristics of vinca. A pot experiment was conducted in the plastics house of the Research Institute for Spice and Medicinal Crops from November 1997 to March 1998. Factorial experiment consisted two factors and three replications was arranged in a randomized block design. Ihe irst factor consisted of two vinca varieties, those wee white flowers (WFV) and red flowers of vinca (RFV). While 4 different levels of water stress i.e., (I) 100% ield capacity (FC), (2) 80% FC, (3) 60% FC, and (4) 40% FC were used as the second factor. Parameters used for evaluating the effect of teatment consisted of morphological characteristics such as (I) plant height, (2) number of primary branches, (3) number of leaves, (4) leaf area (5) dry weight of stem, (6) dry weight of leaf, (7) dry weight of flowers and (8) dry weight of roots, and physiological characteristics observed including: (I) percentages of opened stomata and (2) free proline content of leaf. Results showed that interaction between varieties and water stress did not significantly affect the morphological nor physiological characteristics. Varieties significantly affected the morphological characteristics (except plant height), however they did not signiicantly affect physiological characteristics. Water stress significantly affected the morphological (except dry weight of roots) and free proline contents. Under 80% FC, vinca produced the highest growth and dry weight of plant however, the plant growth and dry weight wee inhibited under 60 and 40% FC. Under 40% FC, percentages of opened stomata deceased signiicantly. Moeover, proline content in the leaves signiicantly increased by water stess treatments.